2016
DOI: 10.1038/nchembio.2246
|View full text |Cite
|
Sign up to set email alerts
|

Gephyrin-binding peptides visualize postsynaptic sites and modulate neurotransmission

Abstract: γ-Aminobutyric acid type A and glycine receptors are the major mediators of fast synaptic inhibition in the human central nervous system and are established drug targets. However, all drugs targeting these receptors bind to the extracellular ligand-binding domain of the receptors, which inherently is associated with perturbation of the basic physiological action. Here we pursue a fundamentally different approach, by instead targeting the intracellular receptor-gephyrin interaction. First, we defined the gephyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 58 publications
1
34
0
2
Order By: Relevance
“…A key question for the future is exactly how and when the proposed trimeric LN-2/GARLH4/GABA A R complex interacts with the intracellular scaffold protein gephyrin. While gephyrin is already the best characterised of all intracellular partners of pLGICs, such as GABA A Rs and GlyRs [68], new studies have recently offered insight into the nature of the gephyrin/receptor interactions at atomic and cellular levels [69;70]. These advances were enabled by the development of peptides that disrupt the gephyrin/receptor interaction with high affinity and specificity [71**].…”
Section: Beyond the Agonist-binding Pocket: Discovery Of New Interactmentioning
confidence: 99%
See 1 more Smart Citation
“…A key question for the future is exactly how and when the proposed trimeric LN-2/GARLH4/GABA A R complex interacts with the intracellular scaffold protein gephyrin. While gephyrin is already the best characterised of all intracellular partners of pLGICs, such as GABA A Rs and GlyRs [68], new studies have recently offered insight into the nature of the gephyrin/receptor interactions at atomic and cellular levels [69;70]. These advances were enabled by the development of peptides that disrupt the gephyrin/receptor interaction with high affinity and specificity [71**].…”
Section: Beyond the Agonist-binding Pocket: Discovery Of New Interactmentioning
confidence: 99%
“…These advances were enabled by the development of peptides that disrupt the gephyrin/receptor interaction with high affinity and specificity [71**]. These tools allowed Maric and co-workers [69] to show that GlyR-mediated inhibitory synaptic transmission is impaired by the loss of the interaction between the receptor and the intracellular scaffold (and by the resulting loss of receptor accumulation at the synapse). Another recent report showed that the small molecule antimalarial drug artemisinin can stabilize gephyrin to enhance GABA A R signalling and thereby promote conversion of pancreatic α cells into functional β cells [72].…”
Section: Beyond the Agonist-binding Pocket: Discovery Of New Interactmentioning
confidence: 99%
“…Small organic fluorophores have the smallest footprint if incorporated by site‐specific chemistry on a small carrier . Various approaches exist to reduce the carrier size, such as using genetically encoded tags nanobodies, affimers, aptamers, super‐binding peptides, or rare amino acid side chains.…”
Section: Figurementioning
confidence: 99%
“…Recent proteomic strategies have vastly expanded the protein repertoire of GABAergic synapses to nearly 200 proteins by targeted purification of GABA A Rs, NL2, or gephyrin (collybistin and InSyn1 to a lesser extent) and their respective interactomes (Kang et al, ; Loh et al, ; Nakamura et al, ; Uezu et al, ). Microscopy‐based approaches encompass the fastest growing means of discovery in vitro and in vivo , including optogenetically controlled GABA A Rs (Lin et al, ), two‐photon based GABA photolysis (Oh et al, ), single‐particle‐tracking of receptor diffusion (Petrini and Barberis, ), quantitative super‐resolution imaging of gephyrin (Pennacchietti et al, ) and gephyrin recombinant antibody‐like proteins (Gross et al, ) or fluorescent super‐binding peptides (Maric et al, ). Additionally, proximity ligation assays allow for researchers to detect native protein interactions utilizing widely‐available primary antibodies (Smith et al, ; Tseng et al, ), while emerging single‐molecule fluorescence resonance energy transfer methods (smFRET) have yet to be applied.…”
Section: Technical Advancements and Future Outlookmentioning
confidence: 99%